Modelling the developmental spliceosomal craniofacial disorder Burn-McKeown syndrome using induced pluripotent stem cells. - Katherine A Wood; Charlie F Rowlands; Huw B Thomas; Steven Woods; Julieta O'Flaherty; Sofia Douzgou; Susan J Kimber; William G Newman; Raymond T O'Keefe (PLoS ONE, 2020)
The craniofacial developmental disorder Burn-McKeown Syndrome (BMKS) is caused by biallelic variants in the pre-messenger RNA splicing factor gene TXNL4A/DIB1. The majority of affected individuals with BMKS have a 34 base pair deletion in the promoter region of one allele of TXNL4A combined with a loss-of-function variant on the other allele, resulting in reduced TXNL4A expression. However, it is unclear how reduced expression of this ubiquitously expressed spliceosome protein results in craniofacial defects during development. Here we reprogrammed peripheral mononuclear blood cells from a BMKS patient and her unaffected mother into induced pluripotent stem cells (iPSCs) and differentiated the iPSCs into induced neural crest cells (iNCCs), the key cell type required for correct craniofacial development. BMKS patient-derived iPSCs proliferated more slowly than both mother- and unrelated control-derived iPSCs, and RNA-Seq analysis revealed significant differences in gene expression and alternative splicing. Patient iPSCs displayed defective differentiation into iNCCs compared to maternal and unrelated control iPSCs, in particular a delay in undergoing an epithelial-to-mesenchymal transition (EMT). RNA-Seq analysis of differentiated iNCCs revealed widespread gene expression changes and mis-splicing in genes relevant to craniofacial and embryonic development that highlight a dampened response to WNT signalling, the key pathway activated during iNCC differentiation. Furthermore, we identified the mis-splicing of TCF7L2 exon 4, a key gene in the WNT pathway, as a potential cause of the downregulated WNT response in patient cells. Additionally, mis-spliced genes shared common sequence properties such as length, branch point to 3' splice site (BPS-3'SS) distance and splice site strengths, suggesting that splicing of particular subsets of genes is particularly sensitive to changes in TXNL4A expression. Together, these data provide the first insight into how reduced TXNL4A expression in BMKS patients might compromise splicing and NCC function, resulting in defective craniofacial development in the embryo.